2022
DOI: 10.1186/s12890-022-02158-w
|View full text |Cite
|
Sign up to set email alerts
|

Baseline anemia predicts a poor prognosis in patients with non-small cell lung cancer with epidermal growth factor receptor mutations: a retrospective study

Abstract: Background Anemia is relatively common in cancer patients, and baseline anemia is associated with poor survival in patients with non-small cell lung cancer (NSCLC). However, there is a lack of large-sample studies of patients with NSCLC with epidermal growth factor receptor (EGFR) mutations. Methods We retrospectively analyzed anemia‑related data for patients with NSCLC and EGFR mutations who were admitted to Zhejiang Cancer Hospital from January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…14,15 Also, anemia predicts a poor prognosis in advanced lung cancer. 16,17 In our study, mean values of pack years, PD-L1 (SP263) expression, NLR and LDH were significantly different between early and non-early relapse groups. Also, the proportion of COPD and the mean value of hemoglobin level tended to be higher in the non-early relapse group.…”
Section: Resultsmentioning
confidence: 46%
See 1 more Smart Citation
“…14,15 Also, anemia predicts a poor prognosis in advanced lung cancer. 16,17 In our study, mean values of pack years, PD-L1 (SP263) expression, NLR and LDH were significantly different between early and non-early relapse groups. Also, the proportion of COPD and the mean value of hemoglobin level tended to be higher in the non-early relapse group.…”
Section: Resultsmentioning
confidence: 46%
“…Smoking, age, ECOG PS and TNM staging are widely recognized as the prognostic factors for lung cancer 14,15 . Also, anemia predicts a poor prognosis in advanced lung cancer 16,17 . In our study, mean values of pack years, PD‐L1(SP263) expression, NLR and LDH were significantly different between early and non‐early relapse groups.…”
Section: Resultsmentioning
confidence: 46%
“…Several studies have confirmed that Hb concentrations might be a valuable prognostic indicator for prognosis in various cancers [ 26 29 ]. In OS, this predictive value of Hb concentrations in survival was still controversial [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even among those harboring EGFR mutation in particular, patients with anemia of grade 2 or better had independently longer median OS. 27 Advanced cancer is a systemic in ammatory disease. Its biologic effects, especially through cytokine interference related to high tumor burden would affect the red blood cell production.…”
Section: Discussionmentioning
confidence: 99%